2016
DOI: 10.18063/esp.v1i1.22
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and economic self-sufficiency among low-income jobseekers with physical disability barriers

Abstract: The purpose of this research is to investigate the process of psychological empowerment by way of examining the effects of perceived employment barrier on employment hope, and employment hope on economic self-sufficiency. A structural equation modeling analysis was used with a sample of 517 participants in a job readiness program of a community-based social service organization in Chicago. Results indicate that employment hope mediates the path between perceived barriers and economic self-sufficiency. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…La EE es un factor determinante para el éxito y la expectativa laboral, pues frente a un escenario cambiante, los requerimientos en el mercado laboral son dinámicos y los solicitantes a un empleo deben considerar el aspecto psicológico, la motivación y las actitudes que permiten desenvolverse eficientemente en un ambiente laboral [22]. Este aspecto representado como Esperanza de empleabilidad puede entenderse como autosuficiencia psicológica, la cual complementa la autosuficiencia económica [23].…”
Section: Digitalunclassified
“…La EE es un factor determinante para el éxito y la expectativa laboral, pues frente a un escenario cambiante, los requerimientos en el mercado laboral son dinámicos y los solicitantes a un empleo deben considerar el aspecto psicológico, la motivación y las actitudes que permiten desenvolverse eficientemente en un ambiente laboral [22]. Este aspecto representado como Esperanza de empleabilidad puede entenderse como autosuficiencia psicológica, la cual complementa la autosuficiencia económica [23].…”
Section: Digitalunclassified
“…Findings from previous PSS research generally suggests that barriers tend to negatively affect employment hope (Hong et al, 2018). However, among individuals experiencing severe co‐occurring barriers – that is physical and mental health barriers – barriers were found to positively affect employment hope (Hong et al, 2016). For North Korean defectors, past traumatic experiences – that is repatriation experience (Kim et al, 2019) and longer stay in third countries as a refugee (Lee et al, 2017) being associated with greater risk of PTSD – were found to increase self‐efficacy which in turn increased resilience and reduced psychological trauma (Lim & Han, 2016).…”
Section: Building a New Economic Future With Employment Hopementioning
confidence: 99%